Cyber Security Incident Handling Model In Small Bank - I Wayan Wiasta Guna; Eugene Ario Suradilaga (Sean Institute, 2025)
Bank digitalization is a breakthrough in this era. Almost all banks in Indonesia are competing to implement bank digitalization. However, this presents a new challenge in the form of a security gap called Cyber Security Risk. Ransomware and all the cyber-attacks that have recently occurred in several Banking and Finance areas in Indonesia have forced companies to rethink cybersecurity governance, bringing together all the essential things. Elements of practical cyber defense and risk management. This research aims to ensure that their security strategies and policies are implemented consistently and measurably by developing a Design Cyber Security Incident Response Model Based on DMAB SEOJK 03 2023 on Small Private Japan Bank in Indonesia.